Electrical and Optical Properties of Ge𝑥Si𝟏−𝑥:H Thin Films Prepared by Thermal Evaporation Method - A. A. J. Al-Douri; M. F. A. Alias; A. A. Alnajjar; M. N. Makadsi (Advances in Condensed Matter Physics)
Thin a-Ge𝑥Si1−𝑥:H films were grown successfully by fabrication of designated ingot followed by evaporation onto glass slides. A range of growth conditions, Ge contents, dopant concentration (Al and As), and substrate temperature, were employed. Stoichiometry of the thin films composition was confirmed using standard surface techniques. The structure of all films was amorphous. Film composition and deposition parameters were investigated for their bearing on film electrical and optical properties. More than one transport mechanism is indicated. It was observed that increasing substrate temperature, Ge contents, and dopant concentration lead to a decrease in the optical energy gap of those films. The role of the deposition conditions on values of the optical constants was determined. Accordingly, models of the density of states for the Ge0.5Si0.5:H thin films as pure, doped with 3.5% of Al (p-type) and that doped with 3.5% As (n-type), were proposed.